Monitoring elite soccer players physical performance using real-time data generated by electronic performance and tracking systems - Oliva-Lozano, J. M.; Martín-Fuentes, I.; Granero-Gil, P.; Muyor, J. M. (The Journal of Strength and Conditioning Research, 2022)
The aims of this technical report were to analyze the validity of real-time data collected by electronic performance and tracking systems (EPTS) and investigate the effect of varying real-time receiver's position on the real-time data collected. Physical performance data were collected from professional soccer players using EPTS. In addition, 3 real-time receivers, which were placed in different positions (i.e., central area of the stadium stands and right and left technical areas), were used to collect real-time data. The real-time data collected by each receiver were visualized on SVivo and compared with the data downloaded directly from the device on SPro. The results showed no statistically significant differences between the data collected by the real-time receivers compared with postsession data in any variable (p > 0.05), except for total distance and high-speed running distance covered, which showed significant differences but trivial effect size (p < 0.05; d = 0.01). The coefficient of determination (R2) and intraclass correlation coefficient were greater than 0.97 and 0.99, respectively. Regarding the analysis of varying the receiver's position on the real-time data collected, the results showed that there was no significant effect of the receiver's position on any variable (p > 0.05). Therefore, valid physical performance data may be obtained by real-time tracking systems such as SVivo, regardless of the position of the real-time receivers and distance to the players. Specifically, high-intensity running actions, distances covered at low and high speed, and accelerometer-derived variables such as player load may be accurately tracked by this real-time tracking software.